Single‐Cell Analysis Clarifies Pathological Heterogeneity in Tenosynovial Giant Cell Tumor and Identifies Biomarkers for Predicting Disease Recurrence - Yubin Xie; Chen Chen; Fei Wu; Yiman Peng; Jing Su; Yang Zhao; Hongjie Huang; Zhong Alan Li; Yin Pei; Wencui Li; Yi He; Tianchen Xue; et al. (Advanced Science)
Abstract Diffuse‐type tenosynovial giant cell tumor (D‐TGCT) and localized‐type tenosynovial giant cell tumor (L‐TGCT) share common genomic aberrations and histopathological features, but the former has a more aggressive nature and a higher recurrence rate, leading to worse prognoses for patients. In this study, single‐cell RNA sequencing (scRNA‐seq) on human D‐TGCT and L‐TGCT lesions is conducted to discover transcriptional differences. A unique cluster of tumor cells in D‐TGCT is identified that regulated differentiation of CD34+ fibroblasts into MMP3+ fibroblasts or APOE+ fibroblasts via COL6A3 − (ITGAV + ITGB8) interaction. The APOE+ fibroblasts further activated IL‐1B+CCL20+ macrophages through the CXCL12/CXCR4 axis. IL‐1B+CCL20+ macrophages and MMP3+ fibroblasts participated in local aggression of D‐TGCT. Two effective biomarkers, ROR1 and PRKD1 are also identified and validated, to predict disease recurrence. This study not only clarified the underlying mechanisms of aggressive behavior in D‐TGCT but also provided a theoretical basis and potential targets for intervention into and treatment of this disease.